STUDI POTENSI LIPASE Alcaligenes faecalis UNTUK APLIKASI BIODETERJEN - Layly, Ika Rahmatul; Wiguna, Nita Oktavia (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2016)
In detergent industry, enzymes are used enormously in terms of quantity and economic value. Lipase catalyzes the hydrolysis of triglycerides into diglycerides and monoglycerides by releasing fatty acids. Lipase is produced by bacteria, fungi, and yeasts. This study aims to determine the potential of Alcaligenes faecalis lipase for its application as biodetergen, through stability testing of its lipase activity against detergent components by exposing the enzyme to the commercial detergents, as well as performance testing through washing. Alcaligenes faecalis lipase was produced using Luria Bertani (LB) culture medium supplemented with 1% olive oil inducer. Production is carried out for 24 hours, and the enzyme was harvested at the 18th hour. The harvested enzyme was tested for their stability after being exposed to commercial detergents at a concentration of 1-5%. Results showed that the exposure to the detergents decreased the enzyme activity to 22, 38, 48, 68 and 90%. Performance test showed that the olive oil impurity removal from the fabric was 29%.Keywords: Alcaligenes faecalis Lipase, biodetergent, lipase activities, washing test AbstrakPada industri detergen penggunaan enzim sangatlah besar baik secara jumlah maupun nilai ekonomi. Lipase mengkatalis hidrolisis trigliserida menjadi digliserida dan monogliserida dengan membebaskan asam lemak. Lipase dihasilkan oleh bakteri, jamur, dan yeast. Penelitian ini bertujuan untuk mengetahui potensi lipase Alcaligenes faecalis untuk aplikasi biodeterjen, melalui uji stabilitas aktivitas lipase terhadap komponen deterjen dengan memaparkan terhadap deterjen komersial serta uji kinerja melalui washing test. Lipase Alcaligenes faecalis diproduksi menggunakan media Luria Bertani (LB) dengan penambahan induser minyak zaitun 1%. Produksi dilakukan selama 24 jam dengan waktu pemanenan enzim pada jam ke-18. Enzim yang sudah dipanen diuji stabilitasnya setelah dipapar dengan deterjen komersial pada konsentrasi 1-5%. Berdasarkan hasil pengujian aktivitas setelah dipapar terlihat penurunan aktivitas berturut-turut sebesar 22, 38, 48, 68 dan 90%. Hasil uji kinerja menunjukkan bahwa noda minyak zaitun yang hilang dari kain sebesar 29%.Kata kunci: Lipase Alcaligenes faecalis, biodeterjen, aktivitas lipase, washing test